Interactive Flipbook as a Learning Innovation for Regional Flagship Products Based on Local Wisdom - Hasanah, H; Siahaan, Sardianto Markos; Tibrani, Masagus Mhd.; Opeyemi, Hammed Saheed (Universitas Muhammadiyah Surakarta, 2025)
Instruction in Learning Natural and Social Sciences (NS&SS) within primary education necessitates contextual and engaging innovations. This study aims to develop and evaluate the effectiveness of an interactive flipbook that integrates distinctive regional commodities based on the local wisdom of Musi Banyuasin. This research employs a Research and Development (R&D) approach using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, was implemented with two fifth-grade classes, consisting of an experimental group (n = 30) and a control group (n =31). The research instruments utilised included expert validation rubrics, learner practicality questionnaires (measuring ease of use and clarity of learning activities), and assessments of learning outcomes. The results indicate that the flipbook demonstrated high validity in terms of content, design, and linguistic suitability. Furthermore, user practicality was rated as very high (91.6%). The flipbook proved effective in enhancing learning outcomes, as evidenced by a high N-Gain score in the experimental class (0.73) compared to a low score in the control class (0.14), alongside a significant difference observed in the t-test (p = 0.000 < 0.05). Consequently, this innovation has the potential to serve as an engaging and meaningful pedagogical resource aligned with the demands of twenty-first-century education.